1981
DOI: 10.1002/jsfa.2740320315
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the lipid components of minced carp (Cyprinus carpio) following cooking

Abstract: The changes in weight, moisture, lipid content and composition, thiobarbituric acid (TBA) and carbonyl values were determined in minced carp following cooking by baking and deep-frying. Baked samples lost lipid via drip while the deep-fried samples absorbed oil. Free fatty acids decreased following cooking. Thiobarbituric acid (TBA) values increased following cooking by either method. Antioxidants (TBHQ and BHA) inhibited the production of TBA-reactive compounds though the production of carbonyls during deep-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Various antioxidants have been shown to delay lipid peroxidation in fish, fishery products, and fish feed ingredients such as fish oil (Olcott 1958), fish meal (Lea et a1 1960;March et a1 1961 ;Merwe and Kapp 1961 ;Roux 1962), mackerel skin lipid (Nash and Ackman 1977), shark and mackerel (Younathan et a1 1983), and Indian oil sardines (Shetty et a1 1991). Mai and Kinsella (1981) showed that the antioxidant BHA was effective in extending the storage stability of deep-fried samples of minced carp. Addition of BHT (002%) to salted dried fish cakes (7 YO lipid content) reduced Zthiobarbituric acid (TBA) values by about 50% (Poulter and Disney 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Various antioxidants have been shown to delay lipid peroxidation in fish, fishery products, and fish feed ingredients such as fish oil (Olcott 1958), fish meal (Lea et a1 1960;March et a1 1961 ;Merwe and Kapp 1961 ;Roux 1962), mackerel skin lipid (Nash and Ackman 1977), shark and mackerel (Younathan et a1 1983), and Indian oil sardines (Shetty et a1 1991). Mai and Kinsella (1981) showed that the antioxidant BHA was effective in extending the storage stability of deep-fried samples of minced carp. Addition of BHT (002%) to salted dried fish cakes (7 YO lipid content) reduced Zthiobarbituric acid (TBA) values by about 50% (Poulter and Disney 1978).…”
Section: Introductionmentioning
confidence: 99%